Comparing Family Members’ Expressions Of Grief To That Of Reporters: A Text Mining Analysis Of Sewol Ferry Disaster’s Victims Commemorative Texts (Journal of Namibian Studies : History Politics Culture, 2023)
This paper compared family members’ expression of grief to that of reporters. For this study, we analyzed commemorative letters written by family members and commemorative articles written by reporters on 119 young students who died in the Sewol ferry disaster on April 16, 2014, in South Korea. The findings showed that the bereaved families’ commemorative letters focused on emotional experiences, such as a mother’s earnest maternal love, her hopes that her child would appear in her dreams, the everyday memories she experienced with her children. In contrast, reporters’ commemorative articles expressed the deep loss of the bereaved parents, prayers for their children's safe return, the deceased children’s talents and hopes for the future, and social norms or virtues such as friendship and community service. The theoretical implications on the mourners of how the death of a young child in a tragic disaster is expressed in different sociocultural contexts are discussed.